Comparison of Aberrant Behavior Checklist profiles across Prader–Willi syndrome, Down syndrome, and autism spectrum disorder. Issue 12 (21st December 2018) - Salehi, Parisa; Herzig, Lisa; Capone, George; Lu, Amanda; Oron, Assaf P.; Kim, Soo‐Jeong
Abstract: Prader–Willi syndrome (PWS, OMIM # 176270) and Down syndrome (DS, OMIM #190685) are neurodevelopmental genetic disorders with higher rates of autism spectrum disorder (ASD). The Aberrant Behavior Checklist (ABC) is a caregiver rating scale that assesses maladaptive behaviors. Overlapping symptoms exist between PWS, DS, and ASD, including maladaptive behaviors. We aimed to evaluate ABC profiles between PWS, DS, and ASD alone (without known genetic syndrome). In addition, we hypothesized PWS and DS with a comorbid ASD positive screen or diagnosis would have similar ABC profiles to ASD alone. ABC data from the following cohorts were analyzed: PWS (Seattle Children's Hospital, n  = 28, mean age = 12.8 ± 4.9 years; University of Florida, n  = 35, mean age = 9.3 ± 7.1 years), DS (Johns Hopkins, n  = 406, mean age = 8.1 ± 2.4 years), and ASD (University of Florida, n = 102, mean age = 10.8 ± 3.5 years). ASD alone had significantly higher ABC scores. Subgroups of PWS and DS with a comorbid ASD positive screen or diagnosis had similarities in scores with the ASD only group, with subscale patterns unique to each syndrome. The ABC indicated worse maladaptive behaviors in children with ASD, including those with genetic syndromes. Although more studies are needed to evaluate the utility and the accuracy of the ABC as a tool to screen for ASD in special populations, it may be a useful adjunct in screening those children with PWS or DS who need more in depth ASD evaluation.